Dietary Saturated Fat Is Associated with Larger LDL Particle Size and Reduced CVD Risk in Framingham Offspring Study (P08-128-19). (24th October 2019) - Yuan, Mengjie; Pickering, R Taylor; Singer, Martha; Moore, Lynn
Abstract: Objectives: Small dense LDL particles have been shown to promote atherogenic cardiovascular disease (CVD). Dietary fat type may impact LDL particle size, but few studies have examined the association between fatty acid intake and LDL particle size and CVD risk. Our goal was to examine the association of saturated fatty acid (SFA) intake with LDL particle size and CVD risk in subjects in the Framingham Offspring Study (FOS). Methods: LDL particle profiles were measured by NMR spectroscopic assay during exam visit 4 in the prospective FOS. Dietary fat, carbohydrate and food groups were assessed using 3-day diet records at exams 3 and 5; intakes were adjusted for body weight using the residuals from linear regression models. Multivariable Cox proportional hazards models and generalized linear modeling (GLM) were used to adjust for sex, age, height, pack-years of smoking, fruit and non-starchy vegetable intakes, dairy, LDL particle size, and prevalent hypertension. Results: Subjects were classified into 6 categories using the combined intakes of carbohydrates (<48% vs. ≥48% of calories) and weight-adjusted SFA (<20, 20-<30, ≥30 g/day). Among those with higher carbohydrate intake, increasing levels of dietary SFA were associated with reduced risk of CVD. Specifically, those with the highest SFA intake and higher energy-adjusted carbohydrate intakes had a 56% (CI: 0.24–0.82) lower risk of CVD compared with those who had both low SFA and lower carbohydrate intakes. Moreover, increasing SFA intake among those with higher carbohydrate intakes was also associated with larger LDL particle sizes ( P = 0.04, highest SFA intake vs. lowest SFA intake). Among low-carbohydrate consumers, SFA intake was not associated with risk of CVD, but was still positively associated with larger LDL particle size ( P = 0.0003, highest SFA intake vs. lowest SFA intake). Conclusions: SFA intake was associated with larger LDL particle sizes regardless of carbohydrate intakes. However, a higher SFA intake was only associated with reduced CVD risk among those with higher carbohydrate intakes. Funding Sources: National Dairy Council.